2019
DOI: 10.15575/biodjati.v4i1.4235
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antibacterial Activity of Acorus calamus L. Extracts

Abstract: Staphylococcus aureus and Escherichia coli are among the most common species of gram-positive and gram-negative bacteria, which cause vaginitis, in infertile women. The Calamus rhizome (Acorus calamus L.) is an Indonesian plant that has antibacterial properties that can be used to treat vaginitis and increase fertility. The aim of this study was to determine the phytochemical and antibacterial activity of the calamus rhizoma in polar, semi-polar and non-polar solvents in the growth of S. aureus and E. coli. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
0
0
Order By: Relevance
“…The plant extract of A. calamus however, showed zone of inhibition against E. coli at only the highest concentration of 200mg/ml with 11mm. The limited activity against E.coli was also reported by Muchtaromah et al (2019). The study by Maharjan et al (2013) showed no zone of inhibition against K, pneumoniae and P. aeruginosa, however our study showed zone of inhibition against it at higher concentration.…”
Section: Antimicrobial Activity Of Samples Extractssupporting
confidence: 71%
“…The plant extract of A. calamus however, showed zone of inhibition against E. coli at only the highest concentration of 200mg/ml with 11mm. The limited activity against E.coli was also reported by Muchtaromah et al (2019). The study by Maharjan et al (2013) showed no zone of inhibition against K, pneumoniae and P. aeruginosa, however our study showed zone of inhibition against it at higher concentration.…”
Section: Antimicrobial Activity Of Samples Extractssupporting
confidence: 71%
“… and β-Asarone were identified as the main compounds with antibacterial properties from A. calamus in all parts of the plant, roots, rhizomes, and essential oils. The essential oil from the tetraploid form of A. calamus rhizome contains about 95-96% β-Aaron as a component mainly [12,13].…”
Section: Accordingmentioning
confidence: 99%
“…Anti-oxidative and anti-inflammatory can be obtained from various types of plants, one of which is Acorus calamus L. It is a water plant that contains phytochemical compounds such as alkaloids, carbohydrates, flavonoids, tannins, and phenolics (Muchtaromah et al, 2019). With its content of phytochemical compounds, the ethanol extract of A. calamus L. rhizome can prevent the suppression of stressed rats' immune systems in normal rats.…”
Section: Introductionmentioning
confidence: 99%